The Extent Of The Reflection Of The Approach To Competencies In Its Second Generation On The Classroom Competencies Of A Professor Of Physical Education And Sports In Intermediate Education - بن يوب عبد العلي; سهايلية شكري (My University, 2021)
The Object of the study aims to identify the extent of the reflection of the approach to competencies in its second generation on the classroom competencies of a professor of physical education and sports in intermediate education from their point of view, by shedding light on functional, relational, and interpersonal competencies. Physical education and sports in intermediate education in Souk Ahras, we conclude that the approach with competencies in its second generation has a positive reflection on all classroom competencies (functional, relational, personal) of a professor of physical education and sports in intermediate education from their point of view education from their point of view. هدفت الدراسة الى التعرف على مدى انعكاس المقاربة بالكفاءات في جيلها الثاني على الكفايات الصفية لأستاذ التربية البدنية والرياضية في التعليم المتوسط من وجهة نظرهم، وذلك من خلال تسليط الضوء على الكفايات الوظيفية، العلائقية، الشخصية، ومن أجل التعرف عن هذا الانعكاس قمنا بتصميم إستبيان موجه لأساتذة التربية البدنية والرياضية في التعليم المتوسط بسوق اهراس، وخلصت نتائج الدراسة الى انه للمقاربة بالكفاءات في جيلها الثاني انعكاس ايجابي على جميع الكفايات الصفية (الوظيفية، العلائقية، الشخصية) لأستاذ التربية البدنية والرياضية في التعليم المتوسط من وجهة نظرهم.